K지역 치과 병원에 내원한 일반 성인의 구강 내 치료 상태 실태조사 - 김동열; Dong Yeol Kim (Chiwisaeng gwahakoeji, 2009)
This study carried out the survey of the actual condition targeting 303 patients with execution of treatment after medical examination among patients who visited from January 2, 2008 to December 31, 2008 at dental hospital where is located in K region, and analyzed by using a program of SPSS13.0. The ratio of treatment in posterior was high with 76.9% in central incisor, 62.3% in the 1st bicuspids, and 45.3% in the first permanent molars as for health in the right teeth of maxillary, and with 77.9% in central incisor, 64.4% in the 1st bicuspids, and 47.6% in the first permanent molars as for the left teeth. In the lower jaw, the ratio of treatment in posterior was high with 92.1% in central incisor, 73.9% in the 1st bicuspids, and 42.6% in the first permanent molars as for health in the right teeth, and with 92.1% in central incisor, 75.9% in the 1st bicuspids, and 43.2% in the first permanent molars as for the left teeth. The upper left cuspid was treated in older patients by age(${χ}^2=32.33$, p=0.000), in the more patients with high blood pressure(${χ}^2=12.60$, p=0.000), and in case of systemic disease. The significant difference was shown(${χ}^2=6.37$, p=0.012). The older patients led to being treated cuspid among right teeth in the lower jaw. The significant difference was shown according in the more patients with high blood pressure(${χ}^2=8.26$, p=0.004). The left cuspid in the lower jaw was treated in the older patients by age the statistically significant difference was shown(${χ}^2=12.10$, p=0.007). 본 연구는 K지역에 소재를 둔 치과병원에서 2008년 1월 2일부터 2008년 12월 31일까지 내원 환자 중 검진 후 치료를 실시한 환자 303명을 대상으로 실태조사를 실시하였으며, SPSS13.0 프로그램을 이용하여 분석하였다. 1. 상악에서 치아의 비 치료율은 우측의 경우는 중절치 76.9%, 제1소구치 62.4%, 제1대구치 45.3%로 나타났으며, 좌측의 경우는 중절치 77.9%, 제1소구치 64.4%, 제1대구치 47.6%로 나타났다. 2. 하악에서 치아의 비 치료율은 우측의 경우는 중절치 92.1%, 제1소구치 73.9%, 제1대구치 42.6%로 나타났으며, 좌측의 경우는 중절치 92.1%, 제1소구치 75.9%, 제1대구치 43.2%로 나타났다. 3. 상악 우측 견치는 연령이 많은 환자일수록 (${χ}^2=13.32$, p=0.004) 고혈압이 있는 환자 (${χ}^2=8.73$, p<0.003)일수록 전신질환이 있는 경우 치료를 하였으며, 통계적으로 유의한 차이를 보였다(${χ}^2=5.19$, p=0.023). 4. 상악 좌측 견치는 연령이 많은 환자일수록 (${χ}^2=32.33$, p=0.000), 고혈압이 있는 환자 (${χ}^2=12.60$, p=0.000)일수록 전신질환이 있는 경우 치료를 하였으며, 통계적으로 유의한 차이를 보였다.(${χ}^2=6.37$, p=0.012). 5. 하악 우측 견치는 고혈압이 있는 환자에서 치료를 하였으며 통계적으로 유의한 차이를 보였다(${χ}^2=8.26$, p=0.004). 6. 하악 좌측 견치는 30대에서 가장 낮게 조사되었으며, 50대 이상의 연령대에서 가장 높게 조사되어 통계적으로 유의한 차이를 보였다(${χ}^2=12.10$, p=0.007).